(3LhGH eSGFd edG cGXe GdSefGfjs - (3GdUbQj, GdeWjQaj, GdGMSGFj, GdHMQGfj, YeGO GdOjf, CMeO Hf Rjf GdOjf Hf EHQGgje Hf UbQ, J (B1241(3g`s ((3eMeO bdj Hf ejQRG GdNhFjfjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3ajbhd GdYHO GdeScjf CMeO Hf Rjf GdOjf GdCMSGFj(B: (3Efg bO cJH Edj HYV GdYGQajf GdWGdHjf ddMbs
(3BNQgG (B:s
(3hCeG YGde GdeKGd hGdCTHGM agh Ydi gPG GdfMh (B...(3hgPg UhQI LSeGfjI aGage(B. (3hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B129s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B185s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds